The effect of 8 weeks of high intensity interval training on Plasma E-selectin levels and white blood cells indicators in cardiovascular patients - محمد محمدی ده چشمه (فیزیولوژی ورزش و فعالیت بدنی)
Abstract aim: cardiovascular disease predictive inflammatory markers are more accurate than lipid profiles in diagnosing diseases. It is important to provide appropriate training pattern in order to reduce the level of inflammatory factors in these patients. The aim of this study was to investigate the effect of 8 weeks of high-intensity interval training on plasma E-selectin levels and white blood cells indices in cardiovascular disease. Methods:: Among patients who voluntary referred to Shahid Rjaie cardiovascular, medical and research center for cardiac rehabilitation, 20 patients (male, 50-70yr) were selected and randomly divided into two groups (n=10): High intensity interval training and control. After determining the VO2peak, subjects in HIIT group performed an interval protocol included 8 intervals of 2 min activity (running on treadmill) at 90% of VO2peak and 2 min active recovery at 30% of VO2peak, three session per week for 8 weeks. Whereas control group have not regular exercise training. Before the training and 48 hours after the last training session fasting blood samples were taken. Independent t-test at p0.05). Conclusions: High intensity interval training led to reducing inflammatory factors levels in cardiovascular patients. Probably part of the beneficial effects of high intensity interval training in cardiovascular disease caused by the inflammatory system adaptation and thus reduction the level of inflammatory factors and cytokines with leukocytes origin.